International Migration and Net Nutrition in the Late 19th and Early 20th Centuries: Evidence from Prison Records - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2021)
In migration studies, immigrant health is a concern before, during, and after migration. This study uses a large late 19th and early 20th century data set of over 20 US prisons to assess migrant net nutrition. Native-born individuals were taller and had the lowest BMIs. International immigrants had lower BMIs and shorter statures. After controlling for other characteristics, native-born females had lower BMIs than men; however, foreign-born women's' BMIs were higher than domestic-born women. Females and males with darker complexions had greater BMIs than their counterparts with fairer complexions.
Keywords: I12; I31; J31; J70; N31; 330; nineteenth century US health; immigrant health; BMI; malnourishment